2018
DOI: 10.1016/j.envres.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Main components of PM10 in an area influenced by a cement plant in Catalonia, Spain: Seasonal and daily variations

Abstract: Particulate matter (PM) composition has a key role in a wide range of health outcomes, such as asthma, chronic obstructive pulmonary disease, lung cancer, cardiovascular disease, and death, among others. Montcada i Reixac, a municipality located in the Barcelona metropolitan area (Catalonia, Spain), for its location and orography, is an interesting case- study to investigate air pollution. The area is also characterized by the presence of different industrial emission sources, including a cement factory and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 54 publications
0
9
0
3
Order By: Relevance
“…'Clean' PM characterization has shown that certain trace elements can be traced to certain type of sources, such as Cobalt Co, Chromium (Cr), Manganese (Mn), and Antimony (Sb) to traffic, and Aluminum (Al), Calcuim (Ca), Nickel (Ni) and Vanadium (V) to cement plant. There variation or constant variation helps to estimate various effects [51]. Particle size distribution of the raw materials shows the primary source of this PM.…”
Section: Pollutants Sources and Classificationmentioning
confidence: 99%
“…'Clean' PM characterization has shown that certain trace elements can be traced to certain type of sources, such as Cobalt Co, Chromium (Cr), Manganese (Mn), and Antimony (Sb) to traffic, and Aluminum (Al), Calcuim (Ca), Nickel (Ni) and Vanadium (V) to cement plant. There variation or constant variation helps to estimate various effects [51]. Particle size distribution of the raw materials shows the primary source of this PM.…”
Section: Pollutants Sources and Classificationmentioning
confidence: 99%
“…Such emissions are related to various diseases such as chronic obstructive pulmonary, silicosis, preterm delivery, etc., according to the relevant review [38]. In Spain, in a similar study by Rovira et al (2018), the direct effect of a cement plant on the environment was reconfirmed; PM 10 and various chemicals were identified such as mineral matter, sea spray, secondary inorganic aerosols, organic matter, elemental carbon and trace elements [39]. In the current study, only a small percentage was attributed to PM 1 (ratio PM 1 /PM 2.5 = 0.33), originating obviously from other activities that took place in parallel during the respective measurements.…”
Section: Resultsmentioning
confidence: 93%
“…In our study, we assumed a mean value of pollutants concentrations as the exposure measure. Depending on the amount of time spent inside buildings, the use of air conditioning or even a small change in environment, these values might not correspond to the actual exposure of a specific individual [34,35]. The exposition differences and subsequent clinical changes were demonstrated for two locations with various characteristic in London [36].…”
Section: Discussionmentioning
confidence: 98%